Association of circulating adiponectin and leptin levels with the risk of diabetic peripheral neuropathy - Chen, Zongcun; Fu, Shasha; Lai, Shuchang; Fu, Maoxiong; Du, Guankui (Frontiers in Endocrinology, 2024)
Background: Adipokines have been implicated in the pathogenesis of type 2 diabetes mellitus (T2DM) and related complications due to their roles in metabolic regulation and inflammation. However, the relationship between these adipokines and diabetic peripheral neuropathy (DPN) remains unclear.Methods: A case-control study was performed with 198 patients with DPN and 205 T2DM patients without DPN from the Endocrinology Department at the Second Affiliated Hospital of Hainan Medical University. Circulating adiponectin and leptin levels were quantified via enzyme-linked immunosorbent assays. Logistic regression models, adjusting for age, sex, BMI, smoking status, and diabetes duration, were applied to evaluate the associations between adiponectin and leptin levels and DPN risk.Results: DPN patients exhibited lower adiponectin (P=0.001) and higher leptin (P=0.007) levels than diabetic controls. Confounders-adjusted analyses revealed that higher adiponectin levels correlated with reduced DPN risk (OR, tertile 3 vs. tertile 1: 0.52; 95% CI: 0.30-0.90), whereas elevated leptin levels were linked to increased DPN risk (OR, tertile 3 vs. tertile 1: 1.91; 95% CI: 1.10-3.32). Stratified analyses confirmed consistent findings across subgroups without statistically significant interactions.Conclusions: Circulating adiponectin and leptin levels correlate with DPN risk in diabetic patients, suggesting their potential as biomarkers for high-risk DPN identification and guiding targeted prevention and management.